Integrated communication and positioning system enabled by fusing visible light and RF - Yanbing YANG; Chao HU; Bangyan LU; Pinpin ZHANG; Yimao SUN; Guanyu CHEN (Tongxin xuebao)
Aiming at the problem that in the hybrid visible light and RF network, such as the traditional user switching scheme leveraging received signal strength and ignoring the user switching error rate, a location-based user switching scheme was proposed.Specifically, an integrated communication and positioning system built upon low-cost IoT chip ESP32 was designed, which could fuse both visible light communication downlink and Wi-Fi uplink signals for accurate user location.A communication and positioning integration framework utilizing time-frequency multiplexing was designed, which used a neural network to estimate the user’s position, and the user completed the switching based on the estimated position.In terms of communication, the throughput of the system can reach up to 35 kbit/s.In terms of positioning, the positioning accuracy of the system can reach 2.8 cm, making a 33% improvement over traditional system.Compared with the switching scheme relying on received signal strength, user switching error rate of the proposed scheme is reduced by 4%.